2009
DOI: 10.1038/labinvest.2009.105
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory role of inducible annexin A2 for impaired biliary epithelial anion-exchange activity of inflammatory cholangiopathy

Abstract: The peribiliary inflammation of cholangiopathy affects the physiological properties of biliary epithelial cells (cholangiocyte), including bicarbonate-rich ductular secretion. We revealed the upregulation of annexin A2 (ANXA2) in cholangiocytes in primary biliary cirrhosis (PBC) by a proteomics approach and evaluated its physiological significance. Global protein expression profiles of a normal human cholangiocyte line (H69) in response to interferon-g (IFNg) were obtained by two-dimensional electrophoresis fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…Proteomic studies from H69 cells have revealed the expression of Annexin A2, a Ca 2 + ‐ and acidic phospholipid‐binding protein and a marker for normal human cholangiocytes . This proteomic study also identified the expression of AE2 and several markers of cholangiocytes in H69 cells . Furthermore, mRNA and protein levels of G‐protein‐coupled receptor 55 were found to be similar in H69, Mz‐ChA‐1, HuCCT cells and human intrahepatic biliary epithelial cells .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Proteomic studies from H69 cells have revealed the expression of Annexin A2, a Ca 2 + ‐ and acidic phospholipid‐binding protein and a marker for normal human cholangiocytes . This proteomic study also identified the expression of AE2 and several markers of cholangiocytes in H69 cells . Furthermore, mRNA and protein levels of G‐protein‐coupled receptor 55 were found to be similar in H69, Mz‐ChA‐1, HuCCT cells and human intrahepatic biliary epithelial cells .…”
Section: Discussionmentioning
confidence: 65%
“…In addition, H69 cells contain Cl ‐ /HCO 3 ‐ anion exchanger 2 (AE2) mRNA and protein and were shown to have AE2‐mediated hydrocholeretic function similar to human cholangiocytes in 3D cultures . Proteomic studies from H69 cells have revealed the expression of Annexin A2, a Ca 2 + ‐ and acidic phospholipid‐binding protein and a marker for normal human cholangiocytes . This proteomic study also identified the expression of AE2 and several markers of cholangiocytes in H69 cells .…”
Section: Discussionmentioning
confidence: 81%
“…ANXA2 has many described functions but its role in the hepato-biliary system is not fully understood. It is expressed in many cells including hepatocytes, HSCs [15] and cholangiocytes [16]. ANXA2 is involved in the plasminogen/plasmin system with fibrinolytic effects promoting clot dissolution in alcoholic liver cirrhosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…ANXA2 is involved in the plasminogen/plasmin system with fibrinolytic effects promoting clot dissolution in alcoholic liver cirrhosis [15]. In inflammatory cholangiopathy ANXA2 can mediate a compensatory effect for the impaired bicarbonate secretion of cholangiocytes through modulation of anion exchanger [16]. ANXA2 has been shown to be expressed as a vitamin D binding protein on hepatocytes and HSCs.…”
Section: Discussionmentioning
confidence: 99%
“…These studies about the understanding of the heterogeneity of cholangiocytes will contribute to answering the key question regarding the selective destruction of bile ducts seen in PBC. Recently, we have applied 2-dimension gel electrophoresis to perform proteomics study (Kido et al 2009). With this sophisticated technique, we found that the expression of annexin A2 was increased in cholangiocytes when exposed to inflammatory cytokines.…”
Section: Primary Biliary Cirrhosis (Pbc)mentioning
confidence: 99%